1996
DOI: 10.1046/j.1365-3083.1996.d01-297.x
|View full text |Cite
|
Sign up to set email alerts
|

Normal Human Immune Peritoneal Cells: Subpopulations and Functional Characteristics

Abstract: Normal human peritoneal cells collected during elective laparatomy from patients with gallbladder stones without clinically detectable inflammatory changes were characterized phenotypically with immunocytochemical method and flow cytometry, with special attention paid to the presence of memory cells. The responsiveness of normal PCs to mitogen and, specifically, the role of peritoneal macrophages in this process was studied. The peritoneal cells consisted of 45% of monocytes/ macrophages (CD68+), as many as CD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
71
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(72 citation statements)
references
References 11 publications
(13 reference statements)
1
71
0
Order By: Relevance
“…Since the mobilization of phagocytes into the peritoneal cavity is similar to that found for tissues (van Furth 1992), the present results indicate, therefore, that in fish, like in mammals (Lehrer et al 1988, Hasslet et al 1989, Silva et al 1989, van Furth 1992, Densen et al 1995, Kubicka et al 1996, macrophages are the tissue resident phagocytes while the neutrophils are present in tissues in significant numbers only in situations of inflammation and only as long as the inflammation persists.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Since the mobilization of phagocytes into the peritoneal cavity is similar to that found for tissues (van Furth 1992), the present results indicate, therefore, that in fish, like in mammals (Lehrer et al 1988, Hasslet et al 1989, Silva et al 1989, van Furth 1992, Densen et al 1995, Kubicka et al 1996, macrophages are the tissue resident phagocytes while the neutrophils are present in tissues in significant numbers only in situations of inflammation and only as long as the inflammation persists.…”
Section: Discussionsupporting
confidence: 83%
“…It is interesting that mammals, teleosts and other higher eukaryotes utilize 2 types of phagocytic cells-neutrophils and macro- 'E-mail: aafonso@gaia.ibmc.up.pt phages-in the defense against infection (Rowley et al 1988, Secombes & Fletcher 1992, Brown 1995. From studies conducted with mammals, data on the behaviour of each of the 2 phagocytes during inflammation, including that caused by infection, can be summarised as follows (Lehrer et al 1988, Haslett et al 1989, Silva et al 1989, van Furth 1992, Densen et al 1995, Kubicka et al 1996. Neutrophils are present in large numbers in blood and hematopoietic organ pools as a reserve, and, under normal conditions, are rare in the tissues and body cavities.…”
Section: Introductionmentioning
confidence: 99%
“…Since some of these cells do not have the phenotypic features of macrophages, a few studies have concluded that the cavity contains a small population of DC representing about 6% of the total cell numbers [13,36]. In this manuscript, we demonstrate for the first time that the peritoneal cavity of both normal human subjects and patients in PD contains a population of CD14 + CD4 + cells that phenotypically, morphologically and functionally fulfills the definition of myeloid DC precursors or pre-DC1.…”
Section: Discussionmentioning
confidence: 68%
“…administration of catumaxomab offers the advantage of a targeted immunotherapy leading to a direct and specific attack on the ascites-causing tumor cells in the peritoneum. Furthermore, all effector cells essential for the antitumor activity of catumaxomab, like T cells and accessory immune cells, are located in the peritoneal cavity (11,12). To target epithelial tumor cells within the peritoneal cavity, EpCAM is an attractive antigen in the otherwise mesenchymal peritoneal compartment.…”
mentioning
confidence: 99%